Pengaruh Inflasi, Jumlah Tenaga Kerja, Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Bali - Salhab, Amira; Soedjono, Lasmini (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 1, Januari 2013 (pp. 1-62), 2012)
GDP is an indicator used to find out  the condition of the economy in a region. The aimsof this study was to find out the effect of inflation, labor, and government spending on Bali economic growth simultaneously and partially. This study used multiple linear regression, the results shows simultaneously and partially have effect on inflation rates, the amount of labor, and government spending significant effect on the Bali economic growth.
Keywords: Inflation; Total Labor; Government Spending; Economic Growth